2004
DOI: 10.1063/1.1739234
|View full text |Cite
|
Sign up to set email alerts
|

Theory of synergy between electron cyclotron and lower hybrid waves

Abstract: A theoretical study of the improvement of the Electron Cyclotron Current Drive (ECCD) efficiency in regimes where most of the current is driven by Lower Hybrid (LH) waves is presented. A perturbation technique is employed to solve the adjoint equation and derive the response function including both collisional and LH effects in the limit where the former dominate. An alternative treatment of the problem, involving a numerical solution of the Langevin equations is proposed to gain insight into the current drive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Moreover, kinetic calculations [9] performed with a 3D Fokker-Planck code have numerically demonstrated an interesting property: the current driven by the simultaneous use of the two waves, I LHEC , can be significantly larger than the sum of the currents separately driven by the two waves, I LH I EC , in the same plasma conditions. This property, hereafter called the synergy effect, has been subsequently confirmed by a different Fokker-Planck code [10], by a self-consistent kinetic-transport code [11], and by analytical calculations [12]. The above-mentioned experiments [3][4][5][6][7][8] have shown that EC waves could couple to the fast electron tail sustained by LH waves and thus provide efficient current ramp-up, despite the fact that in most cases the EC waves absorption took place after multiple reflections on the tokamak walls.…”
mentioning
confidence: 90%
See 3 more Smart Citations
“…Moreover, kinetic calculations [9] performed with a 3D Fokker-Planck code have numerically demonstrated an interesting property: the current driven by the simultaneous use of the two waves, I LHEC , can be significantly larger than the sum of the currents separately driven by the two waves, I LH I EC , in the same plasma conditions. This property, hereafter called the synergy effect, has been subsequently confirmed by a different Fokker-Planck code [10], by a self-consistent kinetic-transport code [11], and by analytical calculations [12]. The above-mentioned experiments [3][4][5][6][7][8] have shown that EC waves could couple to the fast electron tail sustained by LH waves and thus provide efficient current ramp-up, despite the fact that in most cases the EC waves absorption took place after multiple reflections on the tokamak walls.…”
mentioning
confidence: 90%
“…The overall behavior of F syn EC is well reproduced, in particular, the strong reduction for central EC power deposition. As explained later on, this is related to the different values of T e EC and to the different conditions of overlap in velocity space of the two interactions [12].…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…26 . Note that the use here of a second wave is essentially different from other uses of a second wave to optimize the current drive efficiency, [27][28][29][30][31][32][33][34][35] since, rather than promoting absorption by higher velocity electrons, the second wave facilitates the absorption of energy to the LH wave from the α particles. Both methods should lead to an effective increase in the efficiency.…”
Section: Summary and Discussionmentioning
confidence: 99%